An ErbB2/c-Src axis links bioenergetics with PRC2 translation to drive epigenetic reprogramming and mammary tumorigenesis - Harvey W. Smith (Nature Portfolio, 2019)
Polycomb Repressor Complex 2 (PRC2) is frequently up-regulated in cancers. Here, the authors show that the tyrosine kinase c-Src stimulates mitochondrial function to signal energy sufficiency to mTORC1, increasing translation of the PRC2 subunits EZH2 and SUZ12 to support ErbB2-dependent tumours.